Pathologic Outcomes in Men with Low-risk Prostate Cancer Who Are Potential Candidates for Contemporary, Active Surveillance Protocols - Kang, Ho Won (J Korean Med Sci, 2015)
The purpose of this study was to determine whether contemporary active surveillance (AS) protocols could sufficiently discriminate significant from indolent tumors in men with low-risk prostate cancer. We retrospectively analyzed 312 patients with low-risk prostate cancer treated with radical prostatectomy. After exclusion of patients with fewer than 10 cores taken at biopsy and those who received neo-adjuvant treatment, 205 subjects satisfied the final inclusion criteria. Five widely accepted AS protocols were employed in this study. A total of 82.0% of the patients met the inclusion criteria of at least one protocol, and 18% did not meet any criteria of published AS protocols. A significant proportion of patients had non-organ-confined disease (8.6% to 10.6%) or a Gleason score of 7 or greater (18.6% to 23.9%) between the different AS criteria. Among patients who did not meet any AS criteria, 32.4% of patients had a pathologically insignificant cancer. Our results indicated a significant adverse pathology in patients who met the contemporary AS protocols. On the other hand, some patients in whom expectant management would be appropriate did not meet any criteria of published AS protocols. None of the clinical or histological criteria reported to date is able to sufficiently discriminate aggressive tumors from indolent ones. GRAPHICAL ABSTRACT: [Image: see text]